A Cross-Sectional and Longitudinal Study of Novel Metaphor and Metonymy Comprehension in Children, Adolescents, and Adults With Autism Spectrum Disorder - Van Herwegen, Jo; Rundblad, Gabriella (Frontiers in Psychology, 2018)
Previous studies have shown that comprehension of figurative language is impaired in individuals with ASD. However, most studies have focused on lexicalised expressions and have only examined performance at one particular point in time, without examining how performance changes over development. The current study examined the comprehension of novel metaphor and metonymy in individuals with Autism Spectrum Disorders (ASD) from a large age range, using both a cross-sectional (Experiment 1) and longitudinal design (Experiment 2). Performance in the ASD group was lower compared to typically developing (TD) controls, across all ages. Importantly, the results from Experiments 1 and 2 showed that, although chronological age was not a good predictor for performance of either novel metaphor or metonymy in the cross-sectional design, performance improved when longitudinal data was considered. Correlations between vocabulary knowledge, visuo-spatial abilities and figurative language comprehension abilities were also explored.